PLEA BARGAINING AND VICTIM COMPENSATION: A CONSTITUTIONAL APPRAISAL IN INDIA - Chakravarthi, MSHR Teja; K Sitamanikyam (ShodhKosh: Journal of Visual and Performing Arts, 2026)
One of the most significant reforms introduced into the Indian criminal justice system through the Criminal Law (Amendment) Act, 2005 was the incorporation of Chapter XXI-A (Sections 265A–265L) into the Code of Criminal Procedure, 1973.It is a concept that lets the accused person enter a plea of guilty in exchange for a lesser sentence or a disposition that is agreeable by both parties, or to pay restitution to the victim. Though plea bargaining aims at saving time and making justice more efficient, questions have come up about its constitutionality and the features of fair trial, particularly in the context of Article 14, 20(3) and 21 of the Constitution. At the same time, victim compensation has become an important part of contemporary criminal justice, placing a strong focus on restorative justice as a central factor in the system of punishment. This article deals with analysis of Plea bargaining and its constitutional validity in India and its relationship to the victim’s compensation.